Cefepime‐induced encephalopathy: Neural mass modeling of triphasic wave‐like generalized periodic discharges with a high negative component (Tri‐HNC). Issue 1 (12th December 2018) - Tamune, Hidetaka; Hamamoto, Yu; Aso, Naofumi; Yamamoto, Naoki
Abstract : Aim: Cefepime, a fourth‐generation cephalosporin, acts as a GABAA receptor antagonist. Cefepime‐induced encephalopathy (CIE) is frequently overlooked. We aimed to clarify the clinical features, characteristic electroencephalography (EEG), and mechanisms of CIE to aid in its early recognition. Methods: CIE cases documented by a single‐center consultation–liaison team between April 2015 and March 2017 were retrospectively reviewed. For further investigation, neural mass modeling was performed in silico. Results: Three patients with CIE refused medication/examination and showed overt pain, palilalia, and much greater deterioration of eye and verbal response than the motor response, which was possibly related to GABAergic dysfunction. Triphasic wave‐like generalized periodic discharges with a high negative component (Tri‐HNC) were identified on the EEG of all three cases. The simulation reproduced the characteristic feature of 2–3 Hz Tri‐HNC and recovery course on EEG, and a possible involvement of individual differences in pharmacological intervention. It also suggested that auto‐inhibition (synaptic inputs from interneuron to interneuron) dysregulation contributed to generating Tri‐HNC in CIE. Conclusion: As CIE is iatrogenic and continues unless cefepime is stopped, early recognition is crucial. Physicians should be vigilant about altered mental status, pain, and verbal changes in patients taking cefepime. Tri‐HNC on EEG can expedite the diagnosis of CIE, and the association between Tri‐HNC and CIE suggests that an excitatory and inhibitory imbalance due to the dysfunction of GABAergic interneurons is the underlying mechanism. This modeling may offer a new method of investigating disorders related to GABAergic dysfunction.